Strategi Guru dalam Menciptakan Lingkungan Belajar yang Menyenangkan bagi ABK di TK Gamaliel Palu - Krisnawati Patikan; Maria Titik Windarti (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
Inclusive education is a strategic approach in the national education system that aims to provide equal opportunities for all children, including children with special needs, to obtain quality education without discrimination. This study aimed to identify and analyse teachers' strategies in creating a pleasant learning environment for children with disabilities at Gamaliel Kindergarten in Palu, a private Christian value-based school that implements inclusive education. Through a descriptive qualitative approach, data was collected through observation, in-depth interviews and documentation. The results showed that teachers play a central role as facilitators, mentors and creators of an adaptive, contextualised and characterised learning atmosphere. The strategies used include adjusting learning methods, applying the values of love and acceptance, and utilising learning media that are interesting and friendly to children with disabilities. Despite facing challenges such as limited training and facilities, teachers at Gamaliel Kindergarten continue to create a conducive and inclusive learning space. The findings are expected to contribute to the development of inclusive education practices in Indonesia, especially in building child-friendly schools that uphold the values of justice and equality in learning.